Strategi Radio Unit Prambors Medan Dalam Mempertahankan Eksistensinya Sebagai Lembaga Penyiaran Publik - Winda Kustiawan; Ari Oldwin Sitorus; Yaumi Saidah; Ghita Irwanty; Zulhafiz Zulhafiz (Peneliti.net, 2023)
Prambors is a youth streaming radio that plays hits music from Indonesia and the world. This radio presents informative, educative, and entertaining content. The important position of this radio is as a regional media that contains news programs, music, entertainment, to influence the local economic potential. This study aims to understand how the Prambors Medan radio unit's strategy in maintaining its existence as a public broadcasting institution. The theory used in this research is the uses and gratification theory. This research method with a qualitative approach. The data collection techniques were carried out by means of observation and in-depth interviews, the results of research that has been done, have found that technically, Prambors have a strong strategy in social media management. The majority of the Prambors Medan radio broadcast programs are entertainment oriented, targeting young people. However, several programs have informational and educational values ​​that are capable of becoming a forum for the public interest.